TREATMENT OUTCOME OF HCV INFECTED PAEDIATRIC PATIENTS AND YOUNG ADULTS AT KARACHI, PAKISTAN - Aziz, Sina; Rajper, Jamila; Noorulain, Wajeeha (Journal of Ayub Medical College Abbottabad, 2012)
Background: Scanty data are available regarding outcome of children and young adults treated conventionally for Hepatitis C. The present study was undertaken to evaluate the outcome of paediatric and young adult patients treated with PEG-IFN-Î± or conventional interferon (IFN) plus Ribavirin at a public sector hospital of Karachi. Methods: This was an observational study, conducted at Sarwar Zuberi Liver Centre, Civil Hospital Karachi, from 2007 to 2010. Patients up to 20 year of age were tested for Anti-HCV antibodies by 4th generation ELISA and in positive cases HCV RNA was done by PCR. Patients with HBV, HIV and other comorbids such as thalassaemia minor, haemophilia, kidney disease, and co-existing active illness other than HCV were excluded. Depending upon the genotype, patients were treated for 24-48 weeks with IFN 3 MIU Ã—3 per week or PEG-IFN-Î± (1.5 Î¼g/Kg) per week plus Ribavirin 15 mg/Kg/day. Nearly all patients were followed till the end of treatment. Results: Mean age of 55 patients, was 18.42±2.59 years (range 9-20 years) and BMI 19.56±2.36 Kg/m2. Females were 70.9% (n=39). More than 80% had genotype 3 (subtype a or b). Remaining had genotype 1, 4 or mixed. Slight decreases in haemoglobin, platelet and white cell count at 1, 3 and 6 months of treatment were noted. No significant side effects were noted. There was a marked decrease in the ALT post treatment (pre-treatment values 72.69±50.73 versus post-treatment 24.81±14.09 IU/l). End-treatment response (ETR) was 90.9%; of these sustained viral response (SVR) was achieved in 86.3%. Conclusion: HCV infected paediatric and young adult patients treated with PEG-IFN-Î±/or conventional interferon plus Ribavirin (combination therapy) achieved an ETR of 90.9% and SVR of 86.3%. Keywords: HCV, Interferon, Ribavirin, SVR, ETR